The Effect Of Motivation And Creativity On Entrepreneurial Interest Of Students In Entrepreneur Class At Darul Falah Islamic Boarding School - Nafiatul Amara Eka Maulida; Nafi'ah Nafi'ah; Setia Dwi Ratna Rahmawati (JURNAL ECONOMINA, 2026)
This study aims to determine the effect of motivation and creativity on the entrepreneurial interest of Entrepreneur Class students at Darul Falah Islamic Boarding School, Ponorogo. The study used a descriptive quantitative method with a sample of 30 students. Data were analyzed using validity, reliability, classical assumption, multiple linear regression, t-test, and F-test through SPSS version 25. The results showed that motivation had a positive and significant effect on entrepreneurial interest, with a significance value of 0.029 (<0.05). Creativity had a positive effect, but it was not statistically significant, with a significance value of 0.116 (>0.05). Simultaneously, motivation and creativity had a significant effect on entrepreneurial interest, with a significance value of 0.000 (<0.05). The coefficient of determination was 0.498, which means that motivation and creativity were able to explain 49.8% of students’ entrepreneurial interest, while the remaining 50.2% was influenced by other factors outside this study. Therefore, motivation can be considered the most important factor in increasing the entrepreneurial interest of Entrepreneur Class students